Hardware Architecture and Implementation of an AI Pet Robot - Elton Lemos; Abhishek Ghoshal; Aditya Aspat (International Journal of Applied Sciences and Smart Technologies, 2020)
The concept of AI companionship is gaining popularity in recent times. Ourproject is an attempt to create a robotic companion that can act just like apet. We created a Pet Robot that can perform various functions like recognisepeople, recognise objects, recognise emotions, play games, follow a personaround, listen to voice commands, dance and so on. This paper focuses on thehardware aspect of the robot and the working of the Core program (Kernel). Itfurther discusses the algorithm that was implemented in this architecture andcompares the final version with other variations. Our work was able to createa fully functioning AI pet robot by using just cheap commercially availabledevelopment boards, motors and a Desktop PC.